THE POWER OF LAUGHTER: HUMOR, VIOLENCE AND CONSENSUS IN NEW SPAIN. 17TH AND 18TH CENTURIES - Lipsett-Rivera, Sonya (Revista de Historia Social y de las Mentalidades, 2024)
Joking and teasing permeated all aspects of life in New Spain. Using court records from Mexico City and its surrounding communities, this article explores the ways that laughter was deployed within New Spain’s culture of masculinity. Humor was both a means for to relate to each other but also to mark differences. It was a normal part of the day to day interactions of men in New Spain between friends who joked and teased but it could also fall flat when one person did not have the right tone. Yet the border between joking and insulting comments was imprecise and thus often led to conflicts. Laughter brought people together when they were of the same social class but when it was used in an offensive manner, it was transformed into a weapon to assert social distance. Such humor was also part of seductions and similarly had political overtones when it was used in satirical songs. Humor brought people together and created groups of insiders and outsiders. Laughter was a powerful tool within social interactions and provides an alternate way to understand the culture of masculinity in colonial Mexico.